2013
DOI: 10.1136/bmjopen-2013-003666
|View full text |Cite
|
Sign up to set email alerts
|

The chronic kidney disease Water Intake Trial (WIT): results from the pilot randomised controlled trial

Abstract: Background and objectivesIncreased water intake may benefit kidney function. Prior to initiating a larger randomised controlled trial (RCT), we examined the safety and feasibility of asking adults with chronic kidney disease (CKD) to increase their water intake.Design, setting, participants and measurementsBeginning in October 2012, we randomly assigned 29 adults with stage 3 CKD (estimated glomerular filtration rate (eGFR) 30–60 mL/min/1.73 m2 and albuminuria) to one of the two groups of water intake: hydrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 30 publications
1
54
0
1
Order By: Relevance
“…96,97 Currently, there is a randomized trial to determine if supplementation with water to increase urinary output to .3 L/d slows the progression of CKD. 98 Obesity, Metabolic Syndrome, and Hypertension As mentioned, fructose and vasopressin show similar effects to increase fat stores and conserve water (Figure 3). This suggests that transient elevations in serum osmolarity because of either a relative water deficit or a high-sodium diet might be associated with increased risk for obesity and metabolic syndrome.…”
Section: Ckdmentioning
confidence: 99%
“…96,97 Currently, there is a randomized trial to determine if supplementation with water to increase urinary output to .3 L/d slows the progression of CKD. 98 Obesity, Metabolic Syndrome, and Hypertension As mentioned, fructose and vasopressin show similar effects to increase fat stores and conserve water (Figure 3). This suggests that transient elevations in serum osmolarity because of either a relative water deficit or a high-sodium diet might be associated with increased risk for obesity and metabolic syndrome.…”
Section: Ckdmentioning
confidence: 99%
“…We found no significant change in serum osmolality, sodium concentration, eGFR, or quality of life, and no serious events were reported nor observed. This pilot study demonstrated that patients with chronic kidney disease can successfully and safely increase their water intake by 1 to 1.5 l/day over and above the usual fluid intake with no serious adverse effects [10]. Further, to validate the biologic plausibility of our hypothesis, we examined correlations with copeptin (a surrogate marker of vasopressin): at 6 weeks follow-up, copeptin was inversely correlated with both 24 h urine volume and eGFR [12].…”
Section: Figmentioning
confidence: 99%
“…We wished to address the issue of safety in view of clinician concerns about water intoxication in patients with chronic kidney disease [10]; also, with respect to feasibility, only one study with a pre- and post-study questionnaire showed that 11% of participants were unable to increase hydration, 35% produce daily urine volumes of less than 2 l/day, and 30% reported that they were able to increase their water intake only during non-working hours [11]. For these reasons, as well as concerns about regression to the mean, we needed to test the feasibility of whether subjects coached to increase water intake versus those who were coached to maintain normal fluid intake, would have different urine volumes at the end of the pilot study [10]. Because increased hydration can decrease appetite and increase urination, particularly at night, which could negatively affect sleep patterns, we also compared groups on these measures and on their quality of life.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations